Analisis Pengurangan Efek Transien Terhadap Penggunaan Switching Kapasitor Bank Pada Saluran Transmisi 150 KV - Apriyal, Derry; Zakri, Azriyenni Azhari; Feranita, Feranita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The use of bank capacitors in an effort to increase the power factor in power quality issues, has several problems to be aware of. Switching capacitor banks during energization can cause transient surges related to transient voltages and currents. This study discusses the simulation and analysis of more transient voltage due to the switching of bank capacitors that occur in riau transmission line 150 kV using MATLAB Simulink 8.7. The effect of transient state when switching capacitor banks can have a detrimental impact, both for equipment and the system as a whole. Use Synchronous Closing Breaker as one solution to solve this problem. By using Synchronous Closing Breaker can reduce the voltage more in the transient state and dampen the oscillations that occur. The result of simulating the transient voltage value produced on Garuda Sakti bus reaches 1.35 pu, and the use of synchronous closing breaker method can reduce the transient voltage up to 1.04 pu. To reduce transient oscillations, it can also reduce transient current from a value of 532.2 A can be reduced to 476.1 A. The percentage of transient voltage reduction of synchronous closing breaker usage is 22.96%.Keywords: Electric Power System, Transient, synchronous closing breaker, Matlab R2016a/Simulink.